Mainstreaming ICTs: challenges for CTA - Painting, Kevin A. (Technical Centre for Agricultural and Rural Cooperation, 2004)
Kevin Painting outlines the enormous challenges for CTA and its partners in ACP countries in mainstreaming ICTs into their programmes and projects.